Perceived Challenges and Solutions in Implementing E-Learning as Edutainment Approach Among Educators and Students at Selected Universities in Malaysia - Desmond, Cheah Swee Cheong (2023)
Edutainment involves the practice of teaching and learning in a light-hearted and informal setting, utilizing techniques such as role-playing, simulations, and games. Despite e-learning being the primary platform for delivering lessons in current educational institutions, the application of e-learning as an edutainment strategy is comparatively new within Malaysia's educational system. This study aims to investigate the challenges and solutions associated with the implementation of e-learning as an edutainment approach among educators and students at higher educational levels. The study further explores the correlation between educators' and students' demographic data and their perceived challenges in the implementation of e-learning as an edutainment approach. Employing a quantitative methodology, two distinct sets of questionnaires were administered to educators and students, respectively, as research instruments. The sample comprised 170 educators and 350 Bachelor of Arts (BA) students selected from five higher educational institutions in the Klang Valley, Malaysia, using random sampling techniques. Results indicate that both educators (M=4.32) and students (M=4.34) perceive challenges at a high level, while the perceived solutions for educators (M=4.15) and students (M=4.23) also rank at a high level. Chi-Square and Binary Regression analyses reveal that educators' gender, age, teaching experience, and familiarity with edutainment significantly correlate with and predict the perceived challenges in implementing e-learning as an edutainment approach. Conversely, students' gender, age, and familiarity with edutainment do not significantly predict perceived challenges. In conclusion, implementing e-learning through an edutainment approach can be an effective teaching and learning strategy, provided educators and students are equipped to address associated challenges. This study has practical implications for both educators and students, offering a range of solutions to overcome challenges tied to the implementation of e-learning as an edutainment approach.